The role of dynamic enzyme assemblies and substrate channelling in metabolic regulation - Lee J. Sweetlove (Nature Portfolio, 2018)
Temporary association of metabolic enzymes is generally assumed to facilitate substrate channelling within the complex. In this review, Lee Sweetlove and Alisdair Fernie outline the nature and functional consequence of organising enzymes into assemblies, and discuss applications within the natural world and synthetic biology.